Application of the Shifted Frequency Internal Equivalence to Two Dimensional Lossy Objects - Aydemir, B.; Köksal, A. (Advanced Electromagnetics, 2019)
Performance of a new method, Shifted Frequency Internal Equivalence (SFIE) is studied in the analysis of scattering from two dimensional lossy objects. This method finds the solution of a wideband scattering problem faster than classical approaches. By introducing conductivity, loss shows itself as imaginary electrical permittivity. Changing conductivity also changes the distribution of electromagnetic waves and modifies RCS plots. In this study homogeneous and inhomogeneous conductive media are investigated to widen the usage of SFIE method. By increasing conductivity skin effect phenomenon is observed, electrical dimensions are decreased and RCS plots are flattened as expected. Numerical results obtained by SFIE are compared to the ones obtained by Method of Moments and the differences are shown.